A Proposal of the Modification of Japanese Society on Thrombosis and Hemostasis (JSTH) Disseminated Intravascular Coagulation (DIC) Diagnostic Criteria for Sepsis-Associated DIC. (April 2018) - Iba, Toshiaki; Di Nisio, Marcello; Thachil, Jecko; Wada, Hideo; Asakura, Hidesaku; Sato, Koichi; Saitoh, Daizoh
Sepsis-associated disseminated intravascular coagulation (DIC) carries a high risk of death. Thus, a simple tool to quickly establish DIC diagnosis is required. The purpose of this study was to introduce the simple and reliable tool for the prediction of outcome in patients with sepsis complicated by coagulopathy. We investigated the performance of simplified Japanese Society on Thrombosis and Hemostasis (JSTH) DIC diagnostic criteria. In this study, we conducted a retrospective, multicenter survey in 107 general emergency and critical care centers in secondary and tertiary care hospitals. A total of 918 patients with sepsis-associated coagulopathy who underwent antithrombin supplementation were examined. The relationships between patient mortality and each of the baseline (ie, before treatment) JSTH-DIC diagnostic criteria were examined. A reduced platelet count, increased prothrombin time (PT) ratio, and lower antithrombin activity were correlated with 28-day mortality, while fibrinogen and fibrin degradation product (FDP) level were not. Thus, the number of points assigned to FDP levels was reduced from 3 to 1 (above 20 μg/mL). The simplified JSTH diagnostic criteria combining platelet count, PT ratio, antithrombin activity, and FDP level (reduction in the maximum score) strongly predicted 28-day mortality and allowed us to diagnose a larger/similar number of patients with DIC as compared to the original JSTH-DIC. The simplified JSTH-DIC diagnostic criteria show a similar performance to JSTH-DIC criteria in patients with septic coagulopathy. The lower number of laboratory markers used in the simplified JSTH-DIC score may increase its applicability and routine use in emergency and critical care setting.